Robotic percutaneous coronary intervention (R-PCI): Time to focus on the pros and cons - E. Thirumurugan; K. Gomathi; P. Swathy; Syed Ali Afrin; R. Karthick (Indian Heart Journal, 2023)
Aim: To assess the safety, efficiency, and device compatibility of the Second Generation Robotic System. Methods: Data on Robot-Assisted PCI (R–PCI) is frequently insufficient in India. Many articles were published in national, non-indexed journals that are not available online and are difficult to obtain. Recognizing these constraints, the current review is intended to compile the available data on this important new innovation technique. This review could encourage future research and serve as a valuable source of information. Results/Conclusion: In terms of procedure efficiency, operator radiation reduction, and safety, the recent implementation and development of second-generation robotic systems have had a significant impact on interventional cardiology. This technology will play a significant role in the future of interventional cardiology as advancements eliminate the need for manual assistance, improve devices compatibility, and expand the use of robotics for telestenting procedures. A larger study demonstrating the safety and feasibility of tele-stenting over greater geographic distances, as well as addressing fundamental technical difficulties, would be required before attempting R–PCI.